Analysis How to Practice The Good Corporate Governance Principles of The Health Personnel In Puskesmas Cikulur, Lebak Banten Province - Permatasari, Putri (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The application of Good Corporate Governance is believed to provide a strategic contribution in improving the performance of health personnel. The principles of GCG include transparency, accountability, responsibility, independence and fairness which are used in this study. This study aimed to analyze the relation between principles of GCG and the performance of health personnel at the Cikulur Primary Health Care. This study used a cross sectional design with 81 research samples consisting of health personnel. Based on the results of the study, principles of transparency, accountability, and independence in GCG significantly related to the performance of health personnel. While other variables such as the principle of accountability and independence are not related. In this research, suggested that in improving performance, all parties in the need to realize the importance of applying the principles of GCG, especially the principles of transparency, accountability and independence. Keywords: Performance, Good Corporate Governance, Health Personnel